Design and Construction of A Self Balancing Robot using Long Range Control Based on NRF24L01 - Sujiwa, Akbar; Suhadata (Universitas PGRI Adi Buana Surabaya, 2023)
At first, robots were created to replace routine human work, requiring a high level of precision, and also to replace humans in dangerous situations. Robots that have the ability to maintain self-balance are called Self Balancing Robots. The Self Balancing Robot is the result of the development of an inverted pendulum model which is positioned on top of a wheeled train. The robot is controlled using a remote control using NRF 24L01 which can be controlled remotely. And to find out the situation in running the robot which is controlled from the remote using To detect the tilt angle of the robot, the MPU6050 sensor is used which is a module that integrates three sensors, namely the gyroscope and accelerometer on three different axes.